Phenomenological Understanding of Hematite Photoanode Performance - João Pina (2021)
The effect of the structural and electronic properties of hematite photoanodes on the charge carrier dynamics was investigated by photoelectrochemistry and transient absorption spectroscopy (TAS). Hematite photoelectrodes were prepared by spray pyrolysis and hydrothermal methods for obtaining films with different thicknesses, morphologies, doping agents, and surface treatments. TAS analyses were performed using standalone photoelectrodes, a three-electrode configuration and in operando. TAS studies revealed that there is a significant electron-hole recombination within the first few hundred picoseconds and smaller amplitude of longer-lived charge carriers, which are responsible for the generated photocurrent observed in photoelectrochemical measurements. The best performing photoelectrodes are Sn-doped hematite thin film annealed at 800 °C and coated with IrO2/RuO2 co-catalyst and the Ti-doped hematite nanowires. The effect of surface treatments, i.e., high-temperature annealing responsible for Sn intrinsic doping and co-catalyst coating, on the electron-hole recombination dynamics is negligible at the picosecond time scale. The TAS studies showed a slower electron-hole recombination after Ti incorporation, increased electron density, and enlarged surface area.